Estimation of compressive and tensioning forces in linear storages of electric power - Georgy N. Tsitsikyan (Krylov State Research Centre, 2021)
Object and purpose of research. Electromagnetic forces in thin-walled coils of toroidal type and common type of different cross-sections (circular, rectangular, disk, spherical) are estimated and compared. Subject matter and methods. Methods of theoretical electric engineering are used. Main results. It is established that forces for toroidal and common coils have different character. First, there is an effect of centripetal compression, secondly, there is an effect of centripetal tensioning. Conclusion. These effects should be taken into account in the coil design, which have to withstand deformation or damage under compressive or tensioning forces.